"I am making it without you, dad": Resilient academic identities of black female university students with absent fathers: An exploratory multiple case study. Issue 2 (24th April 2017) - Zulu, Ncamisile Thumile; Munro, Nicholas
Abstract : This study explored the resilient academic identity constructions of two black father-absent females who were academically successful postgraduate students at a South African University. Using resilience theory and an African metaphysical framework, the study highlights the conversational devices that these two female students used when constructing a resilient academic identity during in-depth conversational interviews with the primary researcher. The findings highlight how paternal absence and related socio-economic effects can serve as a path towards a resilient academic identity construction and be communicated as opportunities for academic success. The study offers novel insight into the phenomenon of paternal absence among two young black female students, how this absence did not seem to yield negative identity and academic achievement outcomes, and the conversational ways in which a resilient academic identity may be constructed.